Institution-Building and Regional Development in Hungary - Kovács, Katalin; CARTWRIGHT, Andrew (Discussion Papers, 2012)
This report analyses the changing institutional structures for regional policy in Hungary from the pre-accession years to the second phase of the post-accession period. The first part of the paper investigates domestic settings for regional pol¬icy providing detailed information about the chosen case study in Southern Transdanubia. The second section examines the three major pre-accession funds and the first National Development Plan, followed by the analysis of the changes brought in by the New Hungary Development Plan 2007-2013. Institution-build¬ing at the regional level stood in the focus of that international comparative re¬search , and this is the broader theme the present report is also centred around. When drawing the picture on accomplishments and constraints of decentralisation in Hungary, document analysis and qualitative research tools were equally used.